ISOLASI DAN KARAKTERISASI RUNUTAN SENYAWA METABOLIT SEKUNDER FRAKSI ETIL ASETAT DARI UMBI BINAHONG (Anredera cordifolia [Tenore] steenis) - Wahyu Diah Proborini; Chaidir Chaidir (Universitas Tribhuwana Tunggadewi Malang, 2016)
Plant secondary metabolites, as products of secondary metabolism, are a tremendous available resource for pharmacy whether traditional or modern medicine system. Binahong (Anredera cordifolia [Tenore] steenis), also known as Madeira vine, is a medicinal plant that has been empirically recognized for several pharmacological compounds. This plant has also been utilized widely in the society for years as anti-oxidant, antiinflammation, anti-fungal, anti-bacteria, anti-diabetic and anti-cancer. Specifically, the research is aiming to identify molecular structure of secondary metabolite compound in ethyl acetate fraction of binahong roots using analytical HPLC while structure elucidation was done by LC-ESI MS, H-NMR and C-NMR. Analytical HPLC of ethyl acetate fraction has showed major peak on its separated derivative fraction, that is coded Ef 1.2 and Ef 1.3, on time retention 37,7 and 37,4 respectively. Considering the significant amount of Ef 1.2 fraction, then it is used in continued analysis rather than Ef 1.3 fraction. In addition, determination of molecular weight using LC-ESI MS resulted the number of molecular weight of Ef 1.2 fraction which is 296,22 Da (m/z). The molecular weight has closest possibility with empirical formula that is loaded from http://www.chemspider.com, is C20H34O. Characterization through H-NMR and C-NMR for its carbon-hydrogen framework was confirmed that the compound of Ef 1.2 is terpenoid named phenanthrena.